Impact of lean and TPM practices on productivity and quality: insights from a peruvian textile SME - Diaz Joussef, Jorge Andres (2025)
The garment manufacturing sector, particularly small and medium-sized enterprises (SMEs), represents a cornerstone of economic and social development. Despite their significance, these enterprises face operational inefficiencies, including high defect rates and limited productivity, exacerbated by resource constraints and inadequate maintenance practices. Previous studies have emphasized the potential of Lean Manufacturing and Total Productive Maintenance (TPM) to address such challenges, yet their application in SMEs remains underexplored. This study aimed to develop and validate an integrated production model incorporating Lean tools such as 5S and work standardization, alongside TPM practices like autonomous maintenance. The model was implemented in a Peruvian textile SME specializing in polo shirts, achieving a 77.63% reduction in defective products and a 27.72% increase in productivity, while improving the 5S compliance level by 83.67%. These findings highlight the practical and economic benefits of the proposed approach, offering a scalable framework for enhancing operational performance in SMEs. Future research should explore its application across diverse industries and regions.